‘Hot stuff’: making food more desirable with animated temperature cues - Zhang, T; Desebrock, C; Okajima, K; Spence, C (Elsevier, 2024)
Nothing beats a comforting image of a bowl of hot soup with whisps of rising steam unless it is the actual soup itself. The current paper investigates the influence of food photography on people’s food expectations. Despite the recognition of the importance of the food temperature depicted in food images, the effectiveness of using visual cues on food photography to indicate temperature and potential managerial outcomes of so doing has barely been researched. This study explored whether the addition of visual temperature cues to food images was effective in activating relevant temperature associations, leading to downstream consequences, including food desirability, freshness perception and willingness to pay (WTP), with a focus on thermal temperature cues. Three online experimental studies were conducted showing that animated traces of steam added to food images not only induced hot temperature perception of the food, but also increased food desirability and freshness perception. Meanwhile, implied animation (i.e., static picture of rising steam) did not produce any such effect. Further, food image appeal was found to be a boundary condition for the effect of hot temperature cues: that is, when the food images is of low appeal, traces of steam which increased hot temperature perception, in turn enhanced freshness perception and food desirability, but not WTP. The effectiveness of animated steam textures crossmodally enhancing thermal temperature perception and food desirability underscores the potential in digital food creation and marketing.